Direct solution-phase synthesis of 1T’ WSe2 nanosheets - Sokolikova,MS; Sherrell,PC; Palczynski,P; Bemmer,VL; Mattevi,C (Nature Communications, 2019)
Crystal phase control in layered transition metal dichalcogenides is central for exploiting their different electronic properties. Access to metastable crystal phases is limited as their direct synthesis is challenging, restricting the spectrum of reachable materials. Here, we demonstrate the solution phase synthesis of the metastable distorted octahedrally coordinated structure (1T’ phase) of WSe2 nanosheets. We design a kinetically-controlled regime of colloidal synthesis to enable the formation of the metastable phase. 1T’ WSe2 branched few-layered nanosheets are produced in high yield and in a reproducible and controlled manner. The 1T’ phase is fully convertible into the semiconducting 2H phase upon thermal annealing at 400 °C. The 1T’ WSe2 nanosheets demonstrate a metallic nature exhibited by an enhanced electrocatalytic activity for hydrogen evolution reaction as compared to the 2H WSe2 nanosheets and comparable to other 1T’ phases. This synthesis design can potentially be extended to different materials providing direct access of metastable phases.